Reaksi Pasar atas Pengumuman Paket Kebijakan Ekonomi Jilid Satu dan Dua Tahun 2015 pada Perusahaan LQ-45 di Bursa Efek Indonesia - Hari Widiyanto (Fakultas Bisnis, 2017)
This research is aimed to determine market reaction as a result of first and second economic package policies announcements in 2015. Market reaction on this study is measured by using the abnormal return. This study used 42 samples of corporation which included in LQ-45 index. The total periods of the events in this study are 11 days. The level of significance of abnormal return will be tested by t-test. The result of this study indicates that the existence of significant abnormal return at period t-3 in first of economic policy package announcement and at period t-3 and t 0 in second economic policy package announcement. It means that the market reacts to both of economic policies package announcement. Abnormal return that existed before announcements indicate that investor following information which related with government policy, from the reaction that existed government should involve entrepreneurs and economic experts to give positive impact to Indonesian economy.